2021
DOI: 10.3390/ijerph18168541
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s Experiences during Hurricane Maria: Impact, Personal Meaning, and Health Care Needs

Abstract: During a disaster, pregnant women are considered among the most vulnerable. Background: On 20 September 2017, the Caribbean was hit by a category 4 hurricane. The purpose of the study was to explore the impact on pregnant women during and after the hurricane regarding access to health care, social services, and support systems. Methods: In-depth interviews were conducted to 10 women that were pregnant during the event. Qualitative inquiry based on the Interpretative Phenomenological Analysis framework was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“… 26 Our observations align with common cultural values in the Puerto Rican community and Hispanics in general, where family relationships are often prioritized before an individual’s well-being. 26 , 31 Similar to other studies exploring people’s experiences post Hurricane Maria, 31 we also found that local communities, including neighbors, local organizations, and clinics, provided support and resources to help patients with their financial, physical, and psychological needs.…”
Section: Discussionsupporting
confidence: 82%
“… 26 Our observations align with common cultural values in the Puerto Rican community and Hispanics in general, where family relationships are often prioritized before an individual’s well-being. 26 , 31 Similar to other studies exploring people’s experiences post Hurricane Maria, 31 we also found that local communities, including neighbors, local organizations, and clinics, provided support and resources to help patients with their financial, physical, and psychological needs.…”
Section: Discussionsupporting
confidence: 82%
“…Hurricane Sandy related power outages were associated with an increase in emergency department visits for pregnancy complications [45]. Two studies examined the effect of hurricane exposure on the usage and access to maternal healthcare and support services [41,42]. The gestational month of the first prenatal care visit was found to be significantly later within the one-year period after Hurricane Michael in Florida [41].…”
Section: Natural Disaster Exposure Studiesmentioning
confidence: 99%
“…The gestational month of the first prenatal care visit was found to be significantly later within the one-year period after Hurricane Michael in Florida [41]. Interviews conducted on pregnant women exposed to Hurricane Maria in Puerto Rico illustrated that women were concerned about losing their pregnancy, worried about not having access to healthcare, and fearful of negative birth outcomes including premature birth [42]. Grech et al determined that the male to female birth ratio increased following Hurricane Katrina [34].…”
Section: Natural Disaster Exposure Studiesmentioning
confidence: 99%
“…Direct comparison between our study and existing literature is difficult given the scarcity of published studies regarding the concern of pregnant women about the effects of fire events on their pregnancy. A study of the experience of pregnant women during Hurricane Maria in the Caribbean reported that pregnant women were worried about losing their pregnancy due to the Hurricane [52]. Our findings highlight the need for emotional support for pregnant women and addressing their concern during landscape fire events, which may have an impact on their pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 71%